Safety of medical adjustment and confirmatory testing in the diagnostic work-up of primary aldosteronism. Issue 4 (October 2019) - Heinrich, Daniel A; Adolf, Christian; Quinkler, Marcus; Holler, Finn; Lechner, Benjamin; Nirschl, Nina; Sturm, Lisa; Görge, Veronika; Beuschlein, Felix; Reincke, Martin
Abstract : Objective: Saline infusion test (SIT) and captopril challenge test (CCT) are standard confirmatory procedures routinely used in the diagnostic work-up of primary aldosteronism (PA). However, side effects and complications during testing have not been systematically studied. Design: We performed a cohort study with patients undergoing SIT and/or CCT in two centers from 2016 until 2018. Methods: We studied 272 study participants with suspected PA enrolled at two outpatient centers in Germany. We assessed the frequency and severity of side effects during adjustment of blood pressure medication and during SIT and CCT. Results: During the adjustment phase prior confirmatory testing, side effects including palpitations, headaches, edema and hypertensive episodes occurred in 18.4% of study participants. Side effects were associated with higher defined daily doses (DDD) ( r = 0.25, P < 0.005), number of antihypertensive drugs ( r = 0.285, P < 0.005) and higher blood pressure ( r = 0.145, P = 0.019). During SIT, 17.5% of study participants had side effects, associated with higher blood pressure (systolic: r = 0.541, P < 0.0005; diastolic: r = 0.426, P < 0.0005) and DDDs ( r = 0.727, P < 0.0005). During CCT, only 1.5% of study participants developed side effects. Conclusions: In contrast to the high rate of side effects during SIT, CCT appears to be the safer test with a very low event rate. This makes CCT especially suitable for severely hypertensive patients.